(untitled) - Sullivan, Michael (Chicago, 2005)
A comprehensive reference, covering standard practices in children's services. Part of "ALA's Fundamentals Series", this overview provides hands-on, proven strategies for those on the front lines, while addressing questions such as: Why are children's services so important? How do they fit into the library overall?
Keywords: Children's libraries,Thư viện thiếu nhi; United States,Hoa Kỳ